Frijol: Investigacion y produccion - López, M.; Fernández, F.; Schoonhoven, Aart van (United Nations Development Programme, 1985)
Those conferences in each discipline of the Bean Program that have had greater acceptance by the participants of the courses carried out at CIAT are presented. The material is grouped into 6 chapters covering topics on plant physiology and morphology, genetics, breeding methods, pathology, diagnosis techniques, diseases and pests, fertilization, management of acid soils, crop association, and diagnosis of field problems. (CIAT)